Calling circles: Network competition with non-uniform calling patterns - Hoernig,S; Inderst,R; Valletti,T (RAND Journal of Economics, 2014)
We introduce a flexible model of telecommunications network competition with nonuniform calling patterns, accounting for the fact that customers tend to make most calls to a small set of similar people. Equilibrium call prices are distorted away from marginal cost, and competitive intensity is affected by the concentration of calling patterns. Contrary to previous predictions, jointly profitmaximizing access charges are set above termination cost in order to dampen competition if calling patterns are sufficiently concentrated. We discuss implications for regulating access charges as well as on and offnet price discrimination.